Administrative and social situation of Kfri district (Salahiya) between the years (1181/1767) -(1334/1918) - Bakr, Aashti Rahman; Hamad, Dr. Payman Abdullah (Sulaimani Journal for Humanities, 2025)
Kfri (Salahiya) is located southeast of the headquarters of the Mosul Brigade, the town of Salahiya is the headquarters, 24 hours away from Kirkuk. The old name of the town was Kafri and the old name of the district was Zangbad. During the Ottoman period, it was one of the most important districts in terms of geography, administration, economy and military. Throughout the Ottoman rule, it was administratively divided into the province of Baghdad and later Mosul. It consisted of two districts and 156 villages. According to the Ottoman calendar, the district had 1088 houses and a population of 1190-2500 people. The people of the district were generally Turks, Kurds and Arabs. The districts of Tuz Khurmatu and Karatapa were Turkish. They spoke Turkish except for their mother tongue The Bani Na'im and Samid were tents. As for the religious composition, the vast majority of the population was Muslim, with only a few Jews and Christians. State property and military administrative units are established by the state according to the needs of the district, the most important of which are the governor, deputy, mufti, finance director, administrative council, judiciary, post and telegraph and Humayun's property department. The Ottoman state has deployed military battalions in the districts and districts to maintain stability and security, especially to remove gangsters and protect postmen during the transfer of mail and merchant convoys. The education system in the religious district of Salahiya consisted of mosques and contemporary schools in separate buildings consisting of the Sabian school, the primary school and the Roshdiya school. In terms of agriculture, the land of the district was fertile and blessed, except for sunflower plants, all kinds of crops were produced, wheat, rice and cloth were exported to Baghdad. Along with agricultural products, Tuz Khurmatu was rich in salt and oil minerals, and the extraction of these minerals was managed by the emir.
Keywords: Salahiya; Ottoman Empire; Administrative Unit; Agriculture; Commerce